Treatment of radioactive liquid waste using Iraqi geological raw materials and zeolite - Sulaymon, Abbas H.; Afaj, Adnan H.; Rasheed, Haidar M. (Nahrain University College of Engineering Journal, 2017)
A radioactive liquid waste contaminated with cesium-137 was found underneath a destructed radioactive waste treatment station in Tuwaytha site 25 km south of Baghdad - Iraq.The appropriate sorbent materials found for the removal of radio cesium-137 were bentonite and modified bentonite with corresponding removal efficiencies of 85% and 91.8% respectively. The favorable batch experimental conditions were found to be 800 rpm stirring speed, 200 mg sorbent mass, 45?m sorbent particle size, and solution temperature of 30 oC for an initial radio cesium concentration of 0.44 mg/l.The BET isotherm model was found to represent the experimental results very well.